Descendants of the modernist museum: tracing the musealisation of Swedish national parks. Issue 1 (1st January 2023) - Fälton, Emelie
Abstract : Swedish national parks face a shift, transforming them from spaces where tourism is a sub-interest into spaces where tourism is a primary focus. Through the establishment of new instructive installations, the intention is to make these parks Europe's most popular nature-based tourism destinations. Such installations construct the non-human world, often depicted as nature, and contribute to shaping human understandings of nature. In this article, I seek to trace, make visible, and problematize how knowledge of nature is put to work and how power operates through these installations, but also how the non-human world is produced visually, and how all of this produces specific ways of seeing it. This is enabled by a discourse analysis with visual ethnographic influences, in which I focus on representations with an emphasis on design, content, and posed rationality. The analysis is designed in a reflexive-explorative manner, where the empirical context leads the analytical direction while the research process and its steps are presented systematically. Through this analysis, I argue that the national parks are transformed into museological organisations similar to the modernist museum, centred around educating visitors by displaying 'real nature, ' and that this has implications for how the non-human world is understood. The most prominent of these is that a distance is promoted between the tourists and the non-human world.